Impact of informatics and new technologies on emergency care environments. - Feied CF; Smith MS; Handler JA; Gillam M; Pietrzak MP (Topics in Emergency Medicine)
Many traditional aspects of emergency care environments are becoming obsolete as new information technologies transform the way medicine is practiced. New facility designs are needed to accommodate modern care processes that are increasingly able to benefit from ubiquitous instant access to information. Improvements in wireless connectivity, tele-presence, personal data and communications devices, information re-use, and process automation all encourage the use of flexible space and may facilitate closer integration of prehospital and hospital-based emergency care.